2020
DOI: 10.12669/pjms.36.4.2025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inflammatory markers in apparently healthy automobile vehicle drivers in response to exposure to traffic pollution fumes

Abstract: Objective: This study aimed to evaluate pattern of markers of inflammation in apparently healthy drivers who exposed to traffic fumes. Methods: This cross-sectional study was conducted from June 2016 to January 2017 at Liaquat University of Medical & Health Sciences (LUMHS), Jamshoro. It looked into the effects of traffic pollutants on markers of inflammation including CRP, Leukocytes count, IL-6, TNF-α, TNF-β of healthy human volunteers. Eighty-seven, apparently healthy, non-smoking automobile vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Three of the methylomic markers (for genes CSF2, IL6, and IL10 ) were described in the section on inflammation and immunity. Briefly, short- and long-term TRAP was associated with hypomethylation of these markers and higher levels of the proteins they encode [58,73,8891,113,115,124,141,162,205,225,235,254,255]. Hypermethylation of one methylomic marker relevant here (related to a gene that encodes interferon gamma ( IFNG )) was associated with short-term TRAP exposure (though short-term BC was associated with hypomethylation) [38,256].…”
Section: Resultsmentioning
confidence: 99%
“…Three of the methylomic markers (for genes CSF2, IL6, and IL10 ) were described in the section on inflammation and immunity. Briefly, short- and long-term TRAP was associated with hypomethylation of these markers and higher levels of the proteins they encode [58,73,8891,113,115,124,141,162,205,225,235,254,255]. Hypermethylation of one methylomic marker relevant here (related to a gene that encodes interferon gamma ( IFNG )) was associated with short-term TRAP exposure (though short-term BC was associated with hypomethylation) [38,256].…”
Section: Resultsmentioning
confidence: 99%
“…Three of the methylomic markers (for the genes CSF2 , IL6 , and IL10 ) were described in the section on inflammation and immunity. Briefly, short- and long-term TRAP was associated with hypomethylation of these markers and higher levels of the proteins they encode [ 61 , 76 , 91 , 92 , 93 , 94 , 115 , 117 , 127 , 128 , 147 , 165 , 204 , 228 , 246 , 247 ]. Hypermethylation of one methylomic marker relevant here (related to a gene that encodes interferon gamma ( IFNG )) was associated with short-term TRAP exposure (though short-term BC was associated with hypomethylation) [ 41 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated that pro-inflammatory markers like TNF-α impart their roles in developing cardiovascular diseases, metabolic syndrome, obesity, type 2 diabetes, insulin resistance, and non-alcoholic fatty liver disease. 10 , 11 The current study was carried out to demonstrate the association between serum TNF-α and MetS characteristics.…”
Section: Discussionmentioning
confidence: 99%